Students' mathematical understanding ability in curved-sided space structure material reviewed from self-confidence through learning with potrame media - Adinda Cahya Fadillah; Nuriana Rachmani Dewi (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study examined the effect of POTRAME, an augmented-reality (AR)-enhanced pop-up book medium, on ninth-grade students’ mathematical understanding of curved-sided three-dimensional shapes and explored differences by self-confidence. A mixed-methods design was employed, with quantitative data collected first, followed by qualitative explanation (Toyon, 2021). The quantitative phase used a quasi-experimental one-group pretest–posttest design involving 25 ninth-grade students from one public junior high school in Semarang City, selected through cluster random sampling (Li et al., 2024). The qualitative phase involved six students representing high, moderate, and low self-confidence categories. The mathematical understanding test and self-confidence questionnaire were validated by three experts and piloted. The test obtained an Aiken’s V of 0.81 and Cronbach’s alpha of 0.79, while the questionnaire obtained an Aiken’s V of 0.83 and Cronbach’s alpha of 0.85, indicating acceptable validity and reliability (Maulana, 2022; Zakariya, 2022). Quantitative data were analyzed using the paired-sample t-test and N-Gain index, while qualitative data were analyzed descriptively through data reduction, display, and conclusion drawing (Rofiah, 2022). Mean scores increased from 14.31 at pretest to 74.96 at posttest, with an N-Gain of 0.71 (high category) and a significant paired-sample t-test result (p < .05). Higher-self-confidence students demonstrated more coherent and systematic conceptual understanding, whereas lower-self-confidence students had greater difficulty organizing solutions. Because the study lacked a control group, the findings indicate an association between POTRAME use and improved mathematical understanding rather than definitive causal effects. The results provide exploratory support for further evaluation of AR-based pop-up book media in geometry instruction.